An Ancillary Sign in the Diagnosis of Bankart and Bankart Variants in Patients With Glenohumeral Instability on Nonarthrographic Magnetic Resonance Imaging: Preglenoid Fat Thickness. Issue 3 (May 2019) - Polat, Gökhan; Oğul, Hayri; Yalcin, Ahmet; Tuncer, Kutsi; Kaya, Serhat; Pirimoğlu, Berhan; Sade, Recep; Kantarci, Mecit
Abstract : Objective: We investigated whether preglenoid fat thickness can be used as an ancillary sign for preliminary diagnosis of Bankart and its variants on nonarthrographic magnetic resonance imaging. Materials and Methods: Sixty-eight anterior dislocation patients were included in this retrospective study. Forty-eight patients with Bankart and its variants, as detected by arthroscopy and magnetic resonance arthrography, were included in the study group. The study group was divided into osseous Bankart, labral Bankart, Perthes, and anterior labroligamentous periosteal sleeve avulsion subgroups. Twenty patients with no detected labral pathologies by arthroscopy and magnetic resonance arthrography were included in the control group. In these patients, preglenoid fat tissue thickness at the anteroinferior portion was measured at the level of the glenoid tubercle. Thickness of preglenoid fat tissue was compared between groups with different labral pathologies and those with normal labrum. Results: The preglenoid fat tissue thickness was 2.65 ± 1.05 mm in the control group and 0.90 ± 0.59 mm in the study group ( P < 0.0001). Patients with preglenoid fat tissue thinner than 1.6 mm showed a significantly increased likelihood of having Bankart and its variants in receiver operating characteristic analysis (sensitivity of 95.8% and specificity of 85%). There was no significant difference in preglenoid fat tissue thickness between the subgroups of the study group (osseous Bankart, labral Bankart, Perthes, and anterior labroligamentous periosteal sleeve avulsion). Conclusion: Preglenoid fat tissue measurement can be used as an ancillary sign in the diagnosis of Bankart and Bankart variants in glenohumeral instability patients.